Implikasi Pembangunan Ekonomi dan Politik yang Buruk terhadap Konflik Lokal dan Terorisme - Savitri, Rohannisa Naja Rachma (Jurnal Diplomasi Pertahanan, 2020)
Economic and political development are expected to be able to bring an optimal distribution of welfare to all levels of society. However, when the policies are not properly organized, this will certainly present economic and political inequality which then becomes the gateway for conflict and violence to arise in the community such as local conflict and terrorism. The purpose of this study is to determine the relation between the poor economic and political development and its implications for the emergence of local conflicts and terrorism. The method used in this research is a qualitative descriptive analysis and library study as a technique in collecting the required data. In addition, this study uses conflict theory and social welfare theory and also uses the concept of economic and political development and the concept of terrorism as a tool to explain the problems of this research. From the research that has been conducted, the researcher then draws the conclusion that the poor implementation of existing policies regarding the economical and political development that occurs has an indication of the occurrence of local conflicts and the emergence of crimes like terrorism. It can be concluded, from observing such events that happened in the past, instability in economic and political development can be a major trigger in the emergence of local conflicts and terrorism.